Proficiency versus lexical processing efficiency as a measure of L2 lexical quality: Individual differences in word-frequency effects in L2 visual word recognition - Baek, Hyunah; Lee, Yunjeong; Choi, Wonil (Memory and Cognition, 2023)
This study investigated Korean-English second language (L2) speakers’ recognition of high- and low-frequency English words and compared two individual difference measures in their role of representing lexical quality in L2: cloze test scores and inverse efficiency scores (IES; response latency corrected for the amount of errors committed), obtained from lexical decision on a separate set of words. Cloze test scores aimed to assess general L2 proficiency, whereas IES was purported to measure lexical processing efficiency. 109 adult Korean-English L2 speakers participated in the study. Results showed significant main effects of word frequency, cloze test scores, and IES on lexical decision times, replicating previous findings and confirming the predictions of the lexical quality hypothesis. Crucially, IES was revealed to be a better measure of individual differences in L2 lexical quality than were cloze test scores. These findings suggest that lexical quality (which can be operationalized in terms of online lexical processing efficiency) comprises a distinct subdomain of language skills on its own, which cannot be measured in full using conventional language proficiency tests.
Keywords: Adult; Humans; Individuality; Language; Multilingualism; Reaction Time; Recognition, Psychology; Cloze test; Inverse efficiency score; L2 word recognition; Lexical quality; Word frequency